Intratumoral BO-112 in combination with radiotherapy synergizes to achieve CD8 T-cell-mediated local tumor control - Helena Escuin-Ordinas; Ignacio Melero; Marisol Quintero; Jose Luis Perez-Gracia; Maite Alvarez; Maria E Rodriguez-Ruiz; Miguel F Sanmamed; Paloma Sanchez-Mateos; Inmaculada Rodríguez López; Irantzu Serrano-Mendioroz; Celia Barrio-Alonso; Eneko Garate-Soraluze; et al. (Journal for ImmunoTherapy of Cancer)
Background Radioimmunotherapy combines irradiation of tumor lesions with immunotherapy to achieve local and abscopal control of cancer. Most immunotherapy agents are given systemically, but strategies for delivering immunotherapy locally are under clinical scrutiny to maximize efficacy and avoid toxicity. Local immunotherapy, by injecting various pathogen-associated molecular patterns, has shown efficacy both preclinically and clinically. BO-112 is a viral mimetic based on nanoplexed double-stranded RNA (poly I:C) which exerts immune-mediated antitumor effects in mice and humans on intratumoral delivery. BO-112 and focal irradiation were used to make the proof-of-concept for local immunotherapy plus radiation therapy combinations.Methods Murine transplantable tumor cell lines (TS/A, MC38 and B16-OVA) were used to show increased immunogenic features under irradiation, as well as in bilateral tumor models in which only one of the lesions was irradiated or/and injected with BO-112. Flow cytometry and multiplex tissue immunofluorescence were used to determine the effects on antitumor immunity. Depletions of immune cell populations and knockout mice for the IFNAR and BATF-3 genes were used to delineate the immune system requirements for efficacy.Results In cultures of TS/A breast cancer cells, the combination of irradiation and BO-112 showed more prominent features of immunogenic tumor cell death in terms of calreticulin exposure. Injection of BO-112 into the tumor lesion receiving radiation achieved excellent control of the treated tumor and modest delays in contralateral tumor progression. Local effects were associated with more prominent infiltrates of antitumor cytotoxic tumor lymphocytes (CTLs). Importantly, local irradiation plus BO-112 in one of the tumor lesions that enhanced the therapeutic effects of radiotherapy on distant irradiated lesions that were not injected with BO-112. Hence, this beneficial effect of local irradiation plus BO-112 on a tumor lesion enhanced the therapeutic response to radiotherapy on distant non-injected lesions.Conclusion This study demonstrates that local BO-112 immunotherapy and focal irradiation may act in synergy to achieve local tumor control. Irradiation plus BO-112 in one of the tumor lesions enhanced the therapeutic effects on distant irradiated lesions that were not injected with BO-112, suggesting strategies to treat oligometastatic patients with lesions susceptible to radiotherapy and with at least one tumor accessible for repeated BO-112 intratumoral injections.